1995
DOI: 10.1038/373347a0
|View full text |Cite
|
Sign up to set email alerts
|

W/kit gene required for interstitial cells of Cajal and for intestinal pacemaker activity

Abstract: The pacemaker activity in the mammalian gut is responsible for generating anally propagating phasic contractions. The cellular basis for this intrinsic activity is unknown. The smooth muscle cells of the external muscle layers and the innervated cellular network of interstitial cells of Cajal, which is closely associated with the external muscle layers of the mammalian gut, have both been proposed to stimulate pacemaker activity. The interstitial cells of Cajal were identified in the last century but their dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
1,150
1
14

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,298 publications
(1,193 citation statements)
references
References 18 publications
23
1,150
1
14
Order By: Relevance
“…The interaction between the kinase receptor and its ligand is essential for the development of melanocytes, erythrocytes, germ cells, mast cells and interstitial cells of Cajal. [12][13][14][15][16] Gain-offunction mutations of the c-kit gene lead to stem cell factor-independent activation of intracytoplasmic signal transduction and finally tumor growth and differentiation. c-kit mutations have been found in mast cell tumors 17 and gastrointestinal stromal tumors (GISTs), 18 which are classified on the basis of About two-thirds of GISTs coexpress CD34 19,20 and/or bcl-2.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between the kinase receptor and its ligand is essential for the development of melanocytes, erythrocytes, germ cells, mast cells and interstitial cells of Cajal. [12][13][14][15][16] Gain-offunction mutations of the c-kit gene lead to stem cell factor-independent activation of intracytoplasmic signal transduction and finally tumor growth and differentiation. c-kit mutations have been found in mast cell tumors 17 and gastrointestinal stromal tumors (GISTs), 18 which are classified on the basis of About two-thirds of GISTs coexpress CD34 19,20 and/or bcl-2.…”
Section: Resultsmentioning
confidence: 99%
“…It is now widely understood that ICC play a vital role in regulating GI motility. ICC generate a pacing signal that drives smooth muscle, mediates neuronal input to smooth muscle, and establishes a smooth muscle membrane potential gradient across the thickness of the circular smooth muscle layer (Huizinga et al, 1995;Farrugia et al, 2003;Strege et al, 2003;Ward et al, 2004;Sanders et al, 2006). Disturbances in ICC distribution have been correlated with GI dysmotilities in animal model systems, and in humans (He et al, 2000(He et al, , 2001Huizinga et al, 2001;Lyford et al, 2002;Sanders et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of ICC in the GI tract may be accomplished using Kit as a selective and specific marker (Huizinga et al, 1995;Burns et al, 1997;Kluppel et al, 1998;Faussone-Pellegrini and Thuneberg, 1999;Komuro, 1999;He et al, 2000He et al, , 2001Lyford et al, 2002) The proto-oncogene c-kit is expressed by ICC located within the tunica muscularis of the GI tract of mice, guinea pigs, rats, dogs, and humans. Antibodies specific for this protein label ICC within GI tissues in several species, including humans, and have been widely utilized to both determine ICC cellular morphology, and to characterize sub-populations of ICC located in distinct layers of the muscular wall of the GI tract (Ward and Sanders, 1992;Ward et al, 1994;Burns et al, 1997;Ozaki et al, 2004;Komuro, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…21 In mice with c-kit mutations (W/ W v ), the myenteric ICC (ICC-MY) networks were grossly underdeveloped in the small intestine, where pacemaker activity was lacking. 22,23 A previous study revealed that corporal SMCs themselves were able to generate Ca 2 þ store-dependent depolarizations and subsequently trigger action potentials. 24 This evidence implies that ICs in corpus cavernosum may have roles other than pacemaker potential generators.…”
Section: Discussionmentioning
confidence: 99%